Waste Financial Value Creation Model: Advancing Sustainable Finance Through Waste-Based Innovation - Ida I Dewa Ayu Yayati Wilyadewi (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
Budget deficits are a burden for local governments. They cannot rely solely on macro-level fiscal policy to alleviate this burden. A progressive fiscal decentralization policy to encourage capital expenditure with a high multiplier effect is needed. This research aims to present a financial innovation to contribute to Denpasar City's original regional revenue. The revenue source is waste, which has burdened both the government and the city's residents. The innovation, titled the Waste Financial Value Creation Model, has been successfully analyzed using a phenomenological approach. The results demonstrate the model's feasibility for implementation in Denpasar City. Further quantitative research is needed to generalize the model. The hope is to obtain tangible value for increasing Denpasar City's original regional revenue.